Evolving Concepts in the Diagnosis and Management of May–Thurner Syndrome - Chamarthy, Murthy R.; Sutphin, Patrick; Anderson, Matthew; Reddick, Mark; Kalva, Sanjeeva P. (Journal of Clinical Interventional Radiology ISVIR, 2017)
May–Thurner syndrome is a common cause of left lower extremity venous thrombosis resulting from repetitive and dynamic compression of the left common iliac vein by the right common iliac artery, commonly seen in young to middle-aged women. The diagnosis requires high clinical suspicion. Computed tomography venography and magnetic resonance venography depict the extent of venous thrombosis and iliac venous compression in patients with underlying thrombotic and nonthrombotic pathologies, respectively. Contrast venography allows detection of acute and chronic thrombus, associated venous obstruction, and collaterals but is of limited value to evaluate the early venous wall abnormalities. Endovascular ultrasound is highly useful to detect early mural changes and accurately quantify venous narrowing. Endovascular intervention with balloon dilatation and stenting with or without pharmacomechanical thrombectomy followed by long-term anticoagulation is the preferred treatment with excellent technical and clinical outcomes. This review focuses on the current understanding of the pathology, clinical presentation, and endovascular management of May–Thurner syndrome.
Keywords: May-Thurner Syndrome; iliac vein compression; stent; IVUS; thrombus; thrombolysis